Using Hermann Gunkel’s Chaoskampf Theory to Examine Bektashi Velayetnames About Struggles with Dragons - Erkan Kalaycı (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Menakıbnames are called velayetnames in Bektashi culture and represent texts that narrate tales of miraculous deeds or keramet performed by prominent figures of a sect. When the first examples of menakıbnames began to be offered in the ancient Islamic world, they aligned with the essential value that good deeds should be praised, describing virtuous actions and exemplary behaviors. However, as Sufism became widespread in the Islamic world, menakıbnames transformed into texts that also detailed the miraculous deeds of the Sufi saints. Examples of the performed miracles were offered through word of mouth in numerous sect circles to glorify the saints of the sect circle from which they originated. The initial oral testimonies were later recorded in writing. These texts encompass vibrant motifs and represent sources of extensive information about the culture, belief structure, social order, and religious beliefs of the period wherein they were inscribed. Velayetnames extol and glorify the deeds of Bektashi saints; an oft-encountered motif in them concerns a fight against a dragon, and numerous examples of these accounts may be cited. The accounts are striking in their descriptions of Bektashi saints grappling with this creature. The mythic form of the dragon as a being of immense power has captured the imaginations of many cultures across the world, including the Turkish. Apart from depicting fights against this mythological entity, the velayetnames convey the underlying allegorical connotation of conflict against a mythic entity represented as a destructive force. This cosmic battle against chaos constitutes a basis for the preservation of the cosmos in its simplest form, the social order. The present study examines this battle between universal order and disorder through the conceptual framework of Hermann Gunkel’s Chaoskampfy.